2019
DOI: 10.1186/s12885-019-6172-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and outcome of the patients with rhabdomyosarcoma of the biliary tree: Experience of the Cooperative Weichteilsarkom Studiengruppe (CWS)

Abstract: Background Biliary rhabdomyosarcoma (RMS) is the most common biliary tumor in children. The management of affected patients contains unique challenges because of the rarity of this tumor entity and its critical location at the porta hepatis, which can make achievement of a radical resection very difficult. Methods In a retrospective chart analysis we analysed children suffering from biliary RMS who were registered in three different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 15 publications
3
19
0
Order By: Relevance
“…Consistent with prior studies, our analysis demonstrates patients with biliary RMS are typically less than 10 years of age with Group III, embryonal disease 4,8,20 . IRS IV was the first study to incorporate staging in addition to grouping as part of RMS risk stratification, and at the time, the biliary tract was considered an unfavorable site for staging 13,21 .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Consistent with prior studies, our analysis demonstrates patients with biliary RMS are typically less than 10 years of age with Group III, embryonal disease 4,8,20 . IRS IV was the first study to incorporate staging in addition to grouping as part of RMS risk stratification, and at the time, the biliary tract was considered an unfavorable site for staging 13,21 .…”
Section: Discussionsupporting
confidence: 82%
“…Meanwhile, in the five patients who were alive with a complete response at the end of therapy, surgery was not radical and was preceded or followed by chemotherapy and RT with no serious sequelae. Additionally, a German cooperative group reported on 12 patients with localized, biliary RMS recommended DPE alone for patients with resectable Group III embryonal disease and DPE followed by RT for patients with Group III alveolar disease or incompletely resectable Group III embryonal disease 8 . Their report demonstrated a 5‐year EFS of 37% (95% CI: 17‐57%); however, direct comparison to our series is difficult as their study included alveolar histology.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The prognosis of patients older than 10 years is significantly worse, which has been suggested by other authors before ( 2 , 27 ). We report a higher prevalence of BRMS in male children, which has been indicated by most, but not all case series before ( 2 5 ). In contrast to previous assumptions ( 28 ), we found that alveolar histology can be present in BRMS and is associated with poor outcome.…”
Section: Discussionsupporting
confidence: 57%
“…Although there exist more than 70 subtypes, it is possible to divide them into two main categories: soft tissue sarcomas (STSs), which are derived from fat, muscle, nerve, sheath and blood vessels, representing less than 1% of all new cancer diagnoses, and bone sarcomas [1,2]. Among STSs, liposarcoma (LPS) and undifferentiated pleomorphic sarcoma are the most common subtypes in adults, while rhabdomyosarcoma is one of the highest incidences of tumors in children [3,4]. Concerning bone sarcomas, Ewing's sarcoma (EWS) is one of the most frequently diagnosed in children together with osteosarcoma (OS), which is also a common subtype in adults as well as chondrosarcoma [5].…”
Section: Introductionmentioning
confidence: 99%